2020
DOI: 10.1016/j.bpj.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

DHHC5 Mediates β-Adrenergic Signaling in Cardiomyocytes by Targeting Gα Proteins

Abstract: S-palmitoylation is a reversible posttranslational modification that plays an important role in regulating protein localization, trafficking, and stability. Recent studies have shown that some proteins undergo extremely rapid palmitoylation/depalmitoylation cycles after cellular stimulation supporting a direct signaling role for this posttranslational modification. Here, we investigated whether β -adrenergic stimulation of cardiomyocytes led to stimulus-dependent palmitoylation of downst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 61 publications
3
44
1
Order By: Relevance
“…Several recent studies have shown that the C-terminal S -acylated cysteines in zDHHC5 ( Fig. 2 ) are important in regulating the distribution of this enzyme between the plasma membrane and internal membranes in nonneuronal cells ( 85 87 ). Indeed, one study reported that S -acylation of these cysteines occurred in response to isoproterenol stimulation, leading to stabilization of zDHHC5 at the plasma membrane ( 85 ).…”
Section: Regulation Of Zdhhc Enzymes By S -Acylatimentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shown that the C-terminal S -acylated cysteines in zDHHC5 ( Fig. 2 ) are important in regulating the distribution of this enzyme between the plasma membrane and internal membranes in nonneuronal cells ( 85 87 ). Indeed, one study reported that S -acylation of these cysteines occurred in response to isoproterenol stimulation, leading to stabilization of zDHHC5 at the plasma membrane ( 85 ).…”
Section: Regulation Of Zdhhc Enzymes By S -Acylatimentioning
confidence: 99%
“…2 ) are important in regulating the distribution of this enzyme between the plasma membrane and internal membranes in nonneuronal cells ( 85 87 ). Indeed, one study reported that S -acylation of these cysteines occurred in response to isoproterenol stimulation, leading to stabilization of zDHHC5 at the plasma membrane ( 85 ). As the C-tail of zDHHC5 is also S -acylated in brain, it will be interesting in future work to investigate the interplay between S -acylation and phosphorylation of the YDNL endocytic motif in regulating activity-dependent trafficking of this enzyme in neurons.…”
Section: Regulation Of Zdhhc Enzymes By S -Acylatimentioning
confidence: 99%
“…Among them, the best described is the mechanism mediated by β -adrenergic receptor ( β -AR)–Gs–adenylate cyclase (AC) pathway ( Baker, 2014 ). Activation of β -AR–Gs–AC plays an important role in increasing heart rate and force of myocardial contraction ( Chen et al, 2020 ; Santulli & Iaccarino, 2016 ). According to our predicted results, VB could regulate β -AR–Gs–AC pathway by targeting Gs (GNAS) and AC (ADCY2 and ADCY5).…”
Section: Discussionmentioning
confidence: 99%
“…Extremely rapid (within minutes) increase of protein S-acylation in response to agonist stimulation has been recently observed in several studies (16,17,28,29). However, the physiological meaning of these changes remained unclear since conventional approaches to study the role of protein S-acylation rely on complete elimination of this modification through site-directed mutagenesis or pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%